Indiana University Bloomington America's Legacy Campus. - Clapacs, J. Terry (Well House Bks., 2021)
"Amid the forested hills of southern Indiana stands one of America's most beautiful college campuses. Indiana University Bloomington: America's Legacy Campus, the new edition, returns the reader to this architectural gem and cultural touchstone. Revised and updated to include new buildings and features of campus life, it is a must have for any Hoosier. The IU Bloomington campus, rich in architectural tradition, harmonious in building scale and materials, and surrounded by natural beauty, stands today as a testimony to careful campus planning and committed stewardship. Planning principles adopted in the very early stages of campus development have been protected, enhanced, and faithfully preserved, resulting in an institution that can truly be called America's Legacy Campus. Lavishly illustrated and brimming with fascinating details, this book tells the story of Indiana University-a tale not only of buildings, architecture, and growth, but of the talented, dedicated people who brought the buildings to life. Completely updated with new buildings and an epilogue, and now even more lavishly illustrated, this new edition is a lasting tribute to the treasure that is Indiana University Bloomington"--